Studi Perbandingan Metode Penentuan Ketinggian Kawat Tanah Pada Switchyard Gardu Induk Konvensional - Adib Chumaidy (Institut Sains dan Teknologi Nasional, 2016)
The intensity total of lightning in Indonesia area, especially in West Java and Banten is quite high, above 100 times / year / 100 km2, so it requires a protection system to prevent interference from lightning strikes, one of which is the shield system. The shield systems of substations is very closely related to the shape of the switchyard. The shield system design is done by adjusting the height of the tower and the ground wire to get the optimum altitude. The definition of an optimal state in this case is limited to the situation where there is the quality that is not beyond the point of tolerance has technical and cost efficiency. Its design is taken as a comparative study between several methods, including Elektrogeometri Theory, Fixed Angle, and Empirical curve. The calculation and analysis concluded that the theory Elektrogeometri with a distance of 28 m and a high tower of 18.994 m is the best choice in the design of system optimization, compared with other theories to meet the quality criteria for distance security shield.